Physicochemical, morphological, and adhesion properties of sodium bisulfite modified soy protein components - Zhang, Lu (Kansas State University, 2009)
Soybean protein modified with sodium bisulfite behaves like latex adhesives, with adhesive strength comparable to formaldehyde-based adhesives. β-conglycinin and glycinin are two major protein components of the adhesive system. The objective of this research was to investigate the effect of sodium bisulfite on the physicochemical, morphological, and adhesion properties of glycinin and β-conglycinin in order to better understand the function of glycinin and β-conglycinin in the formation of the soy latex adhesive. Sodium bisulfite broke the disulfide bonds that linked acidic and basic polypeptides of glycinin, and the reducing effect was enhanced with increasing sodium bisulfite concentration. Although cleavage of disulfide bonds was expected to destabilize proteins, the thermal stability of glycinin increased as the sodium bisulfite concentration increased. Sodium bisulfite modified glycinin had higher surface hydrophobicity, which facilitated hydrophobic interations between molecules and aggregation of glycinin. The balance between hydrophobic interactions and electrostatic forces makes glycinin form unique chain-like structures. Adhesive performance of glycinin dropped significantly at lower sodium bisulfite concentration and then increased as sodium bisulfite concentration increased up to 24 g/L. Excess sodium bisulfite was detrimental to adhesive strength and water resistance. High-molecular-weight aggregates were observed in unmodified β-conglycinin, but these aggregates were dissociated by sodium bisulfite treatment. Similar to glycinin, the thermal stability of β-conglycinin was improved by the modification. However, the denaturation enthalpy of β-conglycinin decreased significantly at high level of sodium bisulfite (36 g/L). The turbidity at pH 4.8 also dropped extensively at the concentration of 36 g/L. The contact angle of β-conglycinin reached its minimum at 6 g/L sodium bisulfite on cherry wood and 24 g/L on glass. Morphology study proved that sodium bisulfite modification made the β-conglycinin solution more dispersed. At pH 9.5, water resistance of β-conglycinin was improved to a small extent by 6 g/L sodium bisulfite. At pH 4.8, adhesive performance was enhanced by 3 g/L and 6 g/L sodium bisulfite. High level of sodium bisulfite at 36 g/L reduced the adhesive performance of β-conglycinin drastically.
Keywords: Soy protein; Sodium bisulfite modification; Glycinin; Hydrophobic properties; B-conglycinin; Electrostatic interactions; Agriculture, General (0473)